2014
DOI: 10.1098/rsob.140045
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ribosomes of the apicoplast and mitochondrion of Plasmodium spp. and predicted interactions with antibiotics

Abstract: Apicomplexan protists such as Plasmodium and Toxoplasma contain a mitochondrion and a relic plastid (apicoplast) that are sites of protein translation. Although there is emerging interest in the partitioning and function of translation factors that participate in apicoplast and mitochondrial peptide synthesis, the composition of organellar ribosomes remains to be elucidated. We carried out an analysis of the complement of core ribosomal protein subunits that are encoded by either the parasite organellar or nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 101 publications
2
57
0
Order By: Relevance
“…This search identified 43 genes (Table – sheet 2 – column A). In support of some enrichment of translation components in this dataset, we found 5 of the 35 predicted mitochondrial ribosomal proteins (Gupta et al , ) in the 43‐gene dataset, while none of them is found in five lists of 43 randomly chosen genes (Table – sheet 2 – columns C‐O). We attempted to localise the protein product of 14 genes from this focused dataset.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…This search identified 43 genes (Table – sheet 2 – column A). In support of some enrichment of translation components in this dataset, we found 5 of the 35 predicted mitochondrial ribosomal proteins (Gupta et al , ) in the 43‐gene dataset, while none of them is found in five lists of 43 randomly chosen genes (Table – sheet 2 – columns C‐O). We attempted to localise the protein product of 14 genes from this focused dataset.…”
Section: Resultssupporting
confidence: 75%
“…Among the above 10 genes we localised to the T. gondii mitochondrion, 4 are predicted to encode mitoribosomal proteins (Table and Fig. A): TGME49_201830/226280/312680 are predicted to encode the mitochondrial large subunit components 54, 28 and 41, respectively, thus we named them Tg mL54, Tg bL28m and Tg mL41; TGME49_203620, while annotated as hypothetical protein in http://ToxoDB.org, is a putative homolog of the mitochondrial small subunit 35 (mS35) (Gupta et al , ; Greber and Ban, ), we, therefore, named it, Tg m S35 . To provide support for this prediction, we tested the gel migration patterns of endogenously triple‐HA tagged Tg m S35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, it must also be stated that the sensitivity of both: mitochondrial and chloroplast ribosomes to chloramphenicol have also been demonstrated in other organisms (Ellis 1968;SmithJohannsen and Gibbs 1972;Margulies and Brubaker 1970;Chrzanowska-Lightowlers et al 1994;Yunis et al 1973;Houtkooper et al 2013;Kearsey and Craig 1981;Stegeman and Hoober 1974). The level of sensitivity of plastid ribosomes to chloramphenicol seems to be a species-specific issue, what have been recently demonstrated by Gupta et al (2014). The protein content and structure of mitochondrial ribosomal machinery of a few species have been compared, among them C. merolae, revealing several species-specific differences.…”
Section: Introductionmentioning
confidence: 94%
“…Translation of genes encoded by the apicoplast and mitochondrion of P. falciparum is mediated by translation factors encoded by the nuclear genome, with the exception of apicoplast‐encoded EF‐Tu. These factors interact with the reduced and divergent ribosomes (Gupta et al ., ) of the parasite organelles. Initiation factors IF1 and IF3, elongation factors EF‐Tu, EF‐Ts and EF‐G and ribosome recycling factor RRF1 functioning in the apicoplast have been characterized recently and IF2, IF3, EF‐Tu, EF‐G and RRF2 have been identified for parasite mitochondrial translation (Biswas et al ., ; Jackson et al ., ; Johnson et al ., ; Gupta et al ., ; Haider et al ., ).…”
Section: Discussionmentioning
confidence: 99%